Assessing vulnerability to climate change impacts in Cambodia, the Philippines and Vietnam an analysis at the Commune and Household level - Mendoza, Maria Emilinda T.; Heng, Naret; Ballaran, Vicente G. Jr. (2014)
The study takes on the framework that vulnerability to climate change depends on the interrelationship of key elements of exposure, sensitivity, and adaptive capacity (Adger, 2006). The general objective of the study is to arrive at an understanding of the community and household vulnerability in three study areas: Kampong Speu in Cambodia, Laguna province in the Philippines, and Thua Thien Hue in Vietnam. Specifically, it aims 1) to measure communes / barangays'; relative vulnerability in the selected study sites; 2) to analyze social vulnerability of local communities in terms of underlying problems; and, 3) to measure and explain the vulnerability of households in relation to their economic and demographic features. Community level and household level surveys were conducted to gather data for the vulnerability analysis, in combination with qualitative data gathering tools such as key informant and in-depth interviews and focused group discussions.

About two thirds of communes/barangays in the studies sites were identified as highly vulnerable. These are mostly communities in lowland and coastal areas: especially communes/barangays with relatively high incidence of poverty; with large areas devoted for agricultural activities and with poor infrastructure facilities. On the other hand, household characteristics found to be related to vulnerability to climate-related risks and hazards include household income, types of livelihood, family size, education of the household head, and the level of exposure to identified hazards. Households living on natural resource-based livelihood are likely to be more vulnerable as these livelihoods are more exposed to and more sensitive to climate hazards. Most poor households are found to be vulnerable. Low adaptive capacity was found to be a key determinant of household vulnerability to climate change across countries.

Women were found to be more vulnerable to climate hazard than men due to limitation in skills and opportunities but they were given more responsibilities in taking care of family member during risk hazard response and rehabilitation periods. An over representation of women during response and rehabilitation periods was found across the study sites.
Keywords: Climate change